Analisis Tingkat Kepatuhan Wajib Pajak UMKM Dalam Pemenuhan Kewajiban Administrasi Perpajakan di Kantor Pelayanan Pajak Pratama Bekasi Barat Tahun 2022 - Silvia; S Pentanurbowo (Jurnal Ilmu Administrasi Publik, 2025)
Taxpayer compliance is a procedural and administrative compliance and conscious action that is necessary to fulfill taxpayer obligations based on applicable tax rules. Taxes are mandatory contributions to the State that are owed, both by individuals and entities that are coercive based on tax laws. Micro, Small and Medium Enterprises (MSMEs) are productive businesses owned by individuals and business entities that have met the criteria as micro businesses. This study aims to analyze the level of compliance of MSME taxpayers in fulfilling taxation, obstacles and efforts made by KPP Pratama Bekasi Barat in 2022. The research method used by the author is qualitative descriptive. The data collection process is carried out through observation, interviews, documentation. The results of the study show that the MSME Compliance Level is still not optimal due to several things, namely; lack of awareness of MSME taxpayers, lack of knowledge of MSME taxpayers, uneven socialization and education, and limited facilities. The efforts made are to carry out socialization, education, and tax classes to taxpayers. Keywords Compliance, UMKM